PENGARUH KEPUASAN KERJA, DISIPLIN KERJA, DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI TENGAH - Muamar, Muamar (Katalogis, 2017)
The Research intends to determine the influence of work satisfaction, work dicipline, and work culture on the official performance in The Department Of Manpower And Transmigration Central Sulawesi Province, both positively and significantly. This research, is considered a survey, and conducted from March to April 2016. Its population consists of 132 officials, who are civil sevants, in The Department Of Manpower And Transmigration and Respondents are selected based on census technique. Data collecting methods are questionnaire, documentation, interviews, and observations. The data used in this research is qualitative and quantitative included the primary and secondary data. Methods of analysis, is multiple regression analysis. The result of the test show that work satisfaction, work discipline, and work culture simultaneously have positive and significant influence on officials performance in the Department Of Manpower And Transmigration Of Central Sulawesi Province. Partial test shows that work satisfactions, work discipline, and work culture partialeously have positive and significant influence on official performance in The Department Of Manpower And Transmigration Central Sulawesi Province.